Global net biome CO2 exchange predicted comparably well using parameter–environment relationships and plant functional types. Issue 8 (9th January 2023) - Famiglietti, Caroline A.; Worden, Matthew; Quetin, Gregory R.; Smallman, T. Luke; Dayal, Uma; Bloom, A. Anthony; Williams, Mathew; Konings, Alexandra G.
Abstract: Accurate estimation and forecasts of net biome CO2 exchange (NBE) are vital for understanding the role of terrestrial ecosystems in a changing climate. Prior efforts to improve NBE predictions have predominantly focused on increasing models' structural realism (and thus complexity), but parametric error and uncertainty are also key determinants of model skill. Here, we investigate how different parameterization assumptions propagate into NBE prediction errors across the globe, pitting the traditional plant functional type (PFT)‐based approach against a novel top‐down, machine learning‐based "environmental filtering" (EF) approach. To do so, we simulate these contrasting methods for parameter assignment within a flexible model–data fusion framework of the terrestrial carbon cycle (CARDAMOM) at a global scale. In the PFT‐based approach, model parameters from a small number of select locations are applied uniformly within regions sharing similar land cover characteristics. In the EF‐based approach, a pixel's parameters are predicted based on underlying relationships with climate, soil, and canopy properties. To isolate the role of parametric from structural uncertainty in our analysis, we benchmark the resulting PFT‐based and EF‐based NBE predictions with estimates from CARDAMOM's Bayesian optimization approach (whereby "true" parameters consistent with a suite of data constraints are retrieved on a pixel‐by‐pixel basis). When considering the mean absolute error of NBE predictions across time, we find that the EF‐based approach matches or outperforms the PFT‐based approach at 55% of pixels—a narrow majority. However, NBE estimates from the EF‐based approach are susceptible to compensation between errors in component flux predictions and predicted parameters can align poorly with the assumed "true" values. Overall, though, the EF‐based approach is comparable to conventional approaches and merits further investigation to better understand and resolve these limitations. This work provides insight into the relationship between terrestrial biosphere model performance and parametric uncertainty, informing efforts to improve model parameterization via PFT‐free and trait‐based approaches. Abstract : Despite their importance for understanding the role of terrestrial ecosystems in a changing climate, forecasts of net biome CO2 exchange are hindered by uncertainty in model parameters. Here, we compare the traditional plant functional type (PFT)‐based parameterization approach to a novel top‐down, machine learning‐based "environmental filtering" (EF) approach. We find that the EF‐based approach matches or outperforms the PFT‐based approach at a narrow majority of vegetated pixels across the globe.